Ataxia-telangiectasia no Brasil: quadro clínico e laboratorial em um estudo multicêntrico - Loekmanwidjaja, Jessica [UNIFESP] (2019)
Objective: evaluate clinical and laboratorial data and treatment in patients with A-T. Methods: cross-sectional and multi-centric study. Questionnaire was filled based in patient’s charges. Were included patients with A-T diagnosis based on ESID criteria that were in current follow-up, who died and those who lost follow-up. Statistical analyses were performed with SPSS 20.0 and STATA 12 software. Results: twentytwo Brazilians centers participated and a total of 123 patients were included. Were female patients 41,5% and 58,5% were male. Consanguinity was reported by 31,1%. All patients had ataxia, being that 80% presented the symptom until the age of 3 years old. Recurrent airway infections were presented in 66,9%. Opportunistic infections and reaction to attenuated virus vaccine was not reported. Proportion of thinness and severe thinness increased with as the patient grow older, as well as liver enzymes (p<0,001). The most prevalent immunodeficiency was IgA partial deficiency (bellow percentile 3 – 56,1%), followed by IgA deficiency (41,4%) and IgG deficiency (26,6%). IgM was elevated in more than half of the patients. CD4+ lymphopenia was observed in 69% of the patients, CD8+ lymphopenia in 51% and 11,5% had B-lymphocytes bellow 2%. The Kaplan-Meier 20-year survival rate was 63,2% and the survival median time was 25 years. Low levels of IgG were marginally significant with decrease in survival probability ((RR = 2,938, IC 95% = 0,963 - 5,971; p = 0,060). Conclusion: this study showed that clinical features in Brazilian A-T patients are similar to the information described worldwide, with little variation. Low levels of IgG can be related to decrease in estimate survival.